Mencegah Fenomena Bulliying pada Masa Dini di Madrasah Ibtida`Iyah Walfajri Lumajang - Inna Sholati; Satuyar Mufid; Aang Burhanuddin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The phenomenon of bulliying can occur anywhere including in schools, both in the form of verbal and physical actions that can have a serious impact on victims and perpetrators. This study aims to describe how to prevent the phenomenon of bulliying at an early age in Madrasah Ibtida'iyah. The research method was conducted using a qualitative approach. Data collection techniques were carried out through observation, interviews and documentation studies. The results showed that the prevention of bulliying phenomenon in early childhood in Madrasah Ibtida'iyah can be done by: a) instilling empathy, tolerance, and mutual respect from an early age; b) establishing clear school rules or anti-bullying regulations, including sanctions for violators; c) training for teachers; d) involving parents; d) class-based approach.